EFFICACY OF PERMEATAL ENDOSCOPIC MYRINGOPLASTY IN INACTIVE (MUCOSAL) CHRONIC OTITIS MEDIA - Niazi, Saleem Asif; Maqbool, Shahzad; Riaz, Yousra; Khan, Zafarullah; Zaman, Shafaq; Akhtar, Rubab (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the efficacy of permeatal ednoscopic myringoplasty, in inactive (mucosal) COM regarding, graft take and hearing improvement. Study Design: Quasi-experimental study. Place and Duration of Study: ENT Department, Pak Emirates Military Hospital, Rawalpindi, from Aug 2019 to Feb 2020. Methodology: This was conducted on a sample size of n=100. Patients having inactive (mucosal) COM with dry central small, medium and large perforations were included. Patients were divided in to three groups on the basis of age, group A 15-30 years, group B 31-45 years and group C 46-60 years. All the patients underwent per-meatal endoscopic myringoplasty, without raising the tympano-meatal flap, under general anesthesia. Patients were followed up over a period of six months. Graft take was assessed by microscopy. Hearing was assessed by Pure Tone Audiometry (PTA) with improvement in air bone gap to 15db as primary end point. Data was collected on structured performa. Data was analyzed using SPSS version 17. Results: In this study, 33 (33%) were males and 67 (67%) were females. Age ranged 15-60 years. Out of 5 patients lost to follow up. A total of 95 completed their follow up. Based on age of the patients, in group A, successful graft take was 100%. In group B, it was 91% & in group C it dropped to 46%. On the basis of tympanic membrane perforation size, the graft success rate in small perforations was 94.8%; in medium sized perforations it was 86.8% and in large sized perforations of tympanic membrane it was........